DAMPAK ALIRAN MODAL ASING TERHADAP STABILITAS SISTEM KEUANGAN INDONESIA - Taufik khurohman Miftahul Mufid; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2026)
This study aims to analyze the effect of foreign capital inflows on financial system stability in Indonesia, proxied by the Non-Performing Loan ratio. The variables employed include Foreign Direct Investment, portfolio investment, exchange rate, inflation, and money supply, using quarterly data for the period 2013Q2–2021Q4. The Autoregressive Distributed Lag method is utilized to examine the impact of foreign capital inflows on financial system stability in both the short run and the long run. The analytical procedures include stationarity testing, optimal lag selection, ARDL model estimation, Bounds Test for cointegration, as well as diagnostic and stability tests of the model. The results indicate the presence of cointegration; in the long run, only inflation has a significant effect on financial stability, while the other variables are insignificant. In the short run, inflation remains significant, whereas the other variables continue to show no significant effect. These findings suggest that Indonesia’s financial system stability is influenced more by domestic macroeconomic factors particularly inflation than by foreign capital inflows, highlighting the importance of inflation control in maintaining banking credit quality.